Study of the interactions of Pd,In with SiO 2 and Al 2O 3 mixed supports as catalysts for the hydrogenation of nitrates in water - Marchesini, Fernanda Albana (2012)
This paper shows that the combination of Al 2O 3 and SiO 2 as supports of Pd and In allows the modulation of the catalytic properties of nitrate hydrogenation in water in order to improve nitrate conversion and decrease the formation of ammonia. Mechanical mixtures of monometallic catalysts subjected to reduction in hydrogen at 450°C are efficient catalysts when Pd is supported on Al 2O 3 and In is supported on SiO 2, thus showing considerably high activity and selectivity to gaseous nitrogen compounds when the proportions are 75 wt.% of Pd/Al 2O 3 and 25 wt.% of In/SiO 2. When these monometallic catalysts are reduced separately and then mixed in situ in the batch reactor, a moderate activity for nitrate reduction is obtained, suggesting that either some migration of In or Pd occurs in solution generating the bimetallic sites that are necessary to activate nitrateions, or that a loose contact between In and Pd is enough to initiate the reaction. This contact could be favored by the opposite pzc of both supports.